Tumor induction in mice after local irradiation with single doses of either carbon-ion beams or gamma rays. (December 2014) - Ando, Koichi; Koike, Sachiko; Ohmachi, Yasushi; Ando, Yutaka; Kobashi, Gen
Abstract: Purpose : To determine the dose-dependent relative biological effectiveness (RBE) for tumor prevalence in mice receiving single localized doses to their right leg of either carbon ions (15, 45 or 75 keV/μm) or 137Cs gamma rays. Methods and materials : A total of 1647 female C3H mice were irradiated to their hind legs with a localized dose of either reference gamma rays or 15, 45 or 75 keV/μm carbon-ion beams. Irradiated mice were evaluated for tumors twice a month during their three-year life span, and the dimensions of any tumors found were measured with a caliper. The tumor induction frequency was calculated by Kaplan-Meier analysis. Results : The incidence of tumors from 50 Gy of 45 keV/μm carbon ions was marginally higher than those from 50 Gy of gamma rays. However, 60 Gy of 15 keV/μm carbon ions induced significantly fewer tumors than did gamma rays. RBE values of 0.87 + 0.12, 1.29 + 0.08 or 2.06 + 0.39 for lifetime tumorigenesis were calculated for 15, 45 or 75 keV/μm carbon-ion beams, respectively. Fibrosarcoma predominated, with no Linear Energy Transfer (LET)-dependent differences in the tumor histology. Experiments measuring the late effect of leg skin shrinkage suggested that the carcinogenic damage of 15 keV/μm carbon ions would be less than that of gamma rays. Conclusions : We conclude that patients receiving radiation doses to their normal tissues would face less risk of secondary tumor induction by carbon ions of intermediate LET values compared to equivalent doses of photons.